Sustainable Digital Transformation in Indonesian Higher Education: The Role of Service Planning and Architecture Strategy within an Agile IT Governance Approach - Johan Reimon Batmetan (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Digital transformation has become a strategic priority for higher education institutions in Indonesia in responding to technological disruption, stakeholder expectations, and institutional competitiveness. However, many universities continue to face challenges in aligning digital initiatives with organizational strategy and adaptive IT governance. This study examines how Service Planning and Architecture Strategy contribute to institutional digital transformation through an Agile IT Governance framework in the Indonesian higher education context. This study uses a single-case study at Manado State University. A qualitative approach using SWOT analysis, IFAS–EFAS evaluation, and portfolio mapping through the McFarlan Strategic Grid. Data were collected through interviews with 12 institutional stakeholders, including university leaders, IT managers, quality assurance representatives, and digital service users, supported by analysis of institutional strategic documents such as IT master plans, governance policies, and digital transformation reports collected between January and June 2025. An IFAS score of 1.4 and an EFAS score of 0.2 position the university in Quadrant I, indicating strong internal capability to pursue an aggressive transformation strategy despite moderate external pressures. Internal strengths include the existence of standardized IT Service Management practices and consistent quality management implementation. However, structural limitations are identified in the absence of formal enterprise architecture standards and the lack of an integrated IT service catalog system. Portfolio mapping shows that 7 out of 9 digital initiatives are concentrated within the Strategic and Key Operational quadrants, confirming IT’s transition from a support function to a value-driving institutional asset. The study concludes that digital transformation in Indonesian universities is significantly enabled by mature service planning but requires strengthened architectural standardization and governance integration to ensure long-term sustainability. Findings indicate strong internal capabilities in IT service management and digital service quality, supporting proactive transformation initiatives. Nonetheless, gaps in enterprise architecture standards and service catalog management pose structural risks to long-term continuity. Portfolio mapping reveals a concentration of initiatives within Strategic and Key Operational domains, signaling the evolving role of IT from operational support to institutional value driver. The study concludes that effective digital transformation in Indonesian universities depends on the alignment of service planning, architecture strategy, and agile governance mechanisms to sustain organizational resilience and strategic adaptability.